Modelling the Interaction between Danoprevir and Mericitabine in the Treatment of Chronic HCV Infection. Issue 4 (May 2016) - Canini, Laetitia; Guedj, Jeremie; Chatterjee, Anushree; Lemenuel-Diot, Annabelle; Smith, Patrick F; Perelson, Alan S
Background: Modelling HCV RNA decline kinetics under therapy has proven useful for characterizing treatment effectiveness. Methods: Here we model HCV viral kinetics (VK) in 72 patients given a combination of danoprevir, a protease inhibitor, and mericitabine, a nucleoside polymerase inhibitor, for 14 days in the INFORM-1 trial. A biphasic VK model with time-varying danoprevir and mericitabine effectiveness and Bliss independence for characterizing the interaction between both drugs provided the best fit to the VK data. Results: The average final antiviral effectiveness of the drug combination varied between 0.998 for 100 mg three times daily of danoprevir and 500 mg twice daily of mericitabine and 0.9998 for 600 mg twice daily of danoprevir and 1, 000 mg twice daily of mericitabine. Using the individual parameters estimated from the VK data collected over 2 weeks, we were not able to reproduce the low sustained virological response rates obtained in a more recent study where patients were treated with a combination of mericitabine and ritonavir-boosted danoprevir for 24 weeks. Conclusions: This suggests that drug-resistant viruses emerge after 2 weeks of treatment and that longer studies are necessary to provide accurate predictions of longer treatment outcomes.